2014
DOI: 10.4028/www.scientific.net/msf.775-776.102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Epoxy Matrix Composites Incorporated with Sugarcane Bagasse Fibers

Abstract: Sugarcane bagasse is a typical waste generated in the production of sugarcane and ethanol. This agro-industrial waste is commonly used as fuel in the industry boiler for the steam and energy generation. However, part of the bagasse waste is disposed and may pollute the environment. The fibers extracted from the sugarcane bagasse have been considered as addition to polymeric composites. In the present work epoxy composites incorporated with 30% in volume of continuous sugarcane bagasse fibers were evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…According to Table 8 and Figure 8 , it is possible to observe a clear tendency of increasing the elastic modulus of the composites as the volumetric fraction of fibers increases, probably because of the higher stiffness of the fibers. Comparing to literature data for the same epoxy resin [ 58 ], only the 30 vol.% CM fiber-reinforced composite showed higher modulus, probably due to difficulties in load transfer in the fiber-matrix interface. On the other hand, the total strain graph, Figure 7 , did not show any significant variation between the different materials, within the standard deviation.…”
Section: Resultsmentioning
confidence: 61%
“…According to Table 8 and Figure 8 , it is possible to observe a clear tendency of increasing the elastic modulus of the composites as the volumetric fraction of fibers increases, probably because of the higher stiffness of the fibers. Comparing to literature data for the same epoxy resin [ 58 ], only the 30 vol.% CM fiber-reinforced composite showed higher modulus, probably due to difficulties in load transfer in the fiber-matrix interface. On the other hand, the total strain graph, Figure 7 , did not show any significant variation between the different materials, within the standard deviation.…”
Section: Resultsmentioning
confidence: 61%
“…[ 9,10 ] Only a few works investigated sugarcane‐filled epoxy composites recently . [ 11–13 ] Monteiro et al [ 13 ] investigated the addition of bagasse waste into epoxy composites as ballistic resistant materials. Their results indicated that the ballistic performance of cost‐competitive bagasse fiber composites was comparable to Kevlar fiber plates used in commercial multilayered armor systems.…”
Section: Introductionmentioning
confidence: 99%
“…Os valores obtidos são similares ao encontrado por Martins et al [9], ao estudar influência da adição de 30% em volume de fibras de bagaço sem seleção de diâmetro. Apesar da melhora no desempenho mecânico dos compósitos reforçados com fibras de bagaço de cana-de-açúcar, quando comparado com compósitos reforçados com outros tipos de fibras, sem seleção de diâmetro, apresentam valores superiores.…”
Section: Discussão Dos Resultados Apresentadosunclassified
“…Geralmente, o bagaço produzido por essas agroindústrias é incinerado ou descartado em locais inapropriados, contribuindo para o aumento da poluição ambiental. Assim sendo, uma alternativa viável para o aproveitamento, bem como a destinação final ambientalmente correta deste resíduo, é a utilização das fibras de bagaço de cana-de-açúcar como agente de reforço em matriz polimérica [8,9].…”
Section: Introductionunclassified